Effect of sintered microporous coating at the evaporator on the thermal performance of a two-phase closed thermosyphon. (March 2019) - Kim, Yeonghwan; Shin, Dong Hwan; Kim, Jin Sub; You, Seung M.; Lee, Jungho
Highlights: Boiling heat transfer in the thermosyphon is enhanced on the microporous coated surface. Condensation heat transfer performance is also affected by the microporous coating. The overall thermal resistance is reduced up to 51% through the microporous coating. Abstract: In this study, the effects of sintered microporous coating at the evaporator on the thermal performance of a two-phase closed thermosyphon (TPCT) are experimentally investigated using distilled water as a working fluid. The TPCT comprises evaporator, adiabatic, and condenser sections, which have an inner diameter of 25 mm and lengths of 300, 300, and 325 mm, respectively. Copper microparticles are sintered on the inner surface of the evaporator to form a 500-μm-thick microporous structure. Boiling and condensation heat transfer coefficients on the microporous coated TPCT are obtained at filling ratios (FRs) ranging from 0.25 to 1.0 and inclination angles ranging from 90° to 5°. The boiling heat transfer coefficient at the microporous coated evaporator is enhanced owing to an increase in the number of nucleation sites and thin film evaporation in the liquid film formed by capillary force through the porous structure, especially at a low FR. The condensation heat transfer is also affected by the microporous coated evaporator due to the increased amount of vapor generation at the low FR. The overall thermal resistance of the microporous coated TPCT is reduced by 51% at an FR of 0.35 and 30% at an FR of 0.75. The TPCT used in this study shows the best thermal performance at inclination angles between 15° and 30° and FRs between 0.2 and 0.4.